Study of removal btx by pseudomonas putida in bioreactor - Mohd Ashraf, Abdul Rahman (2013)
Benzene, toluene and xylene isomers (BTX) are the major components of gasoline which it is used widely as solvents and feedstock by the chemical industry. It became a common environmental contaminant problem that represents a serious threat to groundwater resources and to public health, being both toxic and relatively water soluble compared to other petroleum constituents. The biological treatment that use microorganism such as Pseudomonas putida has been selected because the ability to reduce the hazard of BTX. The objective of this research is to remove the BTX from wastewater using P. putida in a bioreactor. Before starting the experiment, P. putida is prepared by the growth it inside nutrient broth at a suitable temperature and concentration. The bacteria are put in to ratio of benzene, toluene, xylene, benzene-toluene, benzene-xylene, toluene-xylene and BTX solution inside simple conical flask. But the only BTX sample is only running in the fermenter for comparing the growth of bacteria in a conical flask with the growth of bacteria in fermenter. The bacterial growth will be analyzed using UV-Vis Spectrophotometer while concentration BTX after degradation is analyzed by HPLC. From the data obtain, the growth rate of bacteria in toluene sample is higher than other solution. While the growth rate of bacteria in BTX of conical flask is higher than the growth rate of bacteria in BTX of the fermenter. From overall experiment, Toluene is achieved the highest percent of removal compare to percent removal of benzene and xylene. Thus; removal of BTX by bacteria will be a potential biological treatment which it can solve our environmental pollutants in the future